Strategic Analysis of the Resource Management and Financing for Start-ups - Lyu, Wenbo; Zhu, Guangmin (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
Background: In the creation of a startup, the pivotal elements are the acquisition, integration, redistribution, and protection of resources. Each startup's journey reflects a narrative in the art of resource management. Methods: This paper conducts an analysis of the concept, content, type, and strategies of resource management, with a focus on three primary dimensions: resource management, venture financing, and management of intangible assets. The analysis is supplemented by reviewing several typical failure cases in the startup economy to illustrate the consequences of inadequate resource management. Results: The review highlights that improper resource management has been a common factor in the failures examined. By exploring these failures, the paper identifies key missteps and missed opportunities that contributed to the downturns of these startups. Conclusion: With these insights, the paper provides future entrepreneurs with valuable lessons and strategies to enhance the success rate of their ventures, emphasizing the critical role of effective resource management in the startup ecosystem.